Community Size and Network Closure - Allcott, Hunt; Karlan, Dean; Möbius, Markus M; Rosenblat, Tanya S; Szeidl, Adam (American Economic Review, 2007)
Community Size and Network Closure by Hunt Allcott, Dean Karlan, Markus M. Möbius, Tanya S. Rosenblat and Adam Szeidl. Published in volume 97, issue 2, pages 80-85 of American Economic Review, May 2007